Metformin and Intravascular Contrast Media: What to do in Patients Receiving Both: a Narrative Review - Shams, Moghadaseh; Dehghan, Pooneh; Hosseinpanah, Farhad (Novelty in Biomedicine, 2017)
Metformin-associated lactic acidosis (M-ALA) is considered to be one of the complications caused by intravascular contrast media (CM) administration in diabetics especially those with coexisting renal or cardiac impairment. We focused on the necessity and duration of metformin suspension in diabetics with normal or impaired renal function scheduled for CT scan with IV contrast. Searching PubMed, Web of Science, and Scopus databases, we reviewed the latest relevant guidelines as well as articles published from 1994 to 2015. There is no global consensus among different guidelines on the duration of the Metformin suspension before CT scan with IV contrast. Also, lack of substantial evidence supporting M-ALA encourages specialists to take a less conservative approach. It is safe to continue Metformin in patients with normal renal function who have no co-morbidities. In cases of equivocal renal function (30<GFR<60 mL/min/1.73 m2) and also in patients with normal renal function and other co-morbidities, the decision should be made based on the patient’s clinical status. In case of severe renal failure, the use of metformin should be reassessed. Due to the probability of contrast associated nephropathy, laboratory follow up seems to be necessary for all patients.